An investigation on the radiological findings of dental and bone diseases related to jaw trauma in combat sports - Musa Con; Mehmet Yalcin Tasmekteplıgıl; Taner Tunc; Yesim Denız (Türk Spor ve Egzersiz Dergisi)
This study was designed to examine the prevalence of previously experienced maxillofacial injuries in athletes engaging in combat sports and to investigate any possible radiologic findings of dental and bone pathology that can be caused by repetitive head (jaw) impacts. Thirty-two boxers and thirty-two taekwondo athletes and sex- and age-matched non-athletes control group participated in the study. A special questionnaire was used with questions on previously experienced maxillofacial trauma and mouthguard use. Temporomandibular dysfunctions were also examined. Panoramic radiographs of the athletes and control group were examined by two radiologists. Both athlete groups experienced significantly more dental (p lt; 0.059), temporomandibular joint (TMJ) (p lt;0.05) and nasal (p lt;0.05)injury than non-athletes. In addition, boxers experienced more TMJ (p lt;0.05)and nasal injury (p lt;0.05) than taekwondo players. Although most of the athletes (96.9%) wore mouthguards in sports competitions, few of them (9.4%) used the guards while training. Temporomandibular dysfunction (TMD) was mostly examined in combat sport athletes (p lt;0.05; X2=10.494).There was no statistically significant difference between the athletes and the control group for the possible radiologic findings of dental and bone pathology that could be caused by the repetitive head (jaw) impacts on panoramic radiographs (p gt;0.05). Athletes engaging in combat sports, especially boxers, have significantly more maxillofacial injuries. Therefore, they should be educated to use more safety and protective guards not only in competitions but also in training to prevent maxillofacial injury. This is the first report of panoramic findings on dental and bone pathology that could be caused by repetitive head (jaw) impacts.